THE IMPLEMENTATION OF TOEFL PRACTICUM CLASS TOWARD THE RESULT OF STUDENTS’ TOEFL SCORE IN ENGLISH AND LITERATURE DEPARTMENT - Djamereng, Jumharia; Yusuf, Faidah; Nirwana, Nirwana (English Language, Linguistics, and Culture International Journal, 2021)
The policy of many universities regarding to the mandatory of TOEFL test for students has become a new discourse in academic circles, especially from the student's perspective. Although the standards set by each university are different, there are some similar conditions faced by students in meeting these standards such as, TOEFL becoming a burden for students, particularly those with limited English skills, moreover, it is increasing the cost of study by requiring students to pay for the test execution cost. Therefore, in line with this policy, the campus must provide support so that each student can meet the expected qualifications. This study aims to describe how the TOEFL Practicum Class is organized by the English language and literature department to help students meet the TOEFL standard set by the campus, which is 500. The experimental method in this research uses a type of research design with a pretest-posttest control design method, and the total sample used was 64 students from the fifth semester of English and literature department.  this study consists of 3 stages, namely preparation stage, implementation stage and final or evaluation. stages. Based on the findings regarding to the effectiveness of the TOEFL Practicum Class implementation, it can be seen from the results of the pre-test and post-test means score, which seems to have increased toward the score of the students.